Adverse events of immune checkpoint inhibitors for patients with digestive system cancers: A systematic review and meta-analysis - Kou, Liqiu; Wen, Qinglian; Xie, Xiaolu; Chen, Xiu; Li, Jun; Li, Yaling (Frontiers in Immunology, 2022)
Objective: To study the incidence and distribution of adverse events in immune checkpoint inhibitors (ICI) for digestive system cancers and to provide a reference for the safe, rational, and effective use of immune detection site inhibitors. Methods: We searched for articles published in English between January 1, 2010, and May 18, 2022. All clinical trials of ICI-based therapies for digestive system cancers were investigated, including only randomized controlled trials that reported data on the overall incidence of treatment-related adverse events(trAEs) or immune-related adverse reactions(irAEs) or tables. Results: We searched 2048 records, of which 21 studies (7108 patients) were eligible for inclusion. The incidence of ICI trAEs of any grade was 82.7% (95% CI 73.9-90.0), and the incidence of grade 3 or higher trAEs was 27.5% (95% CI 21.3-34.1). The pooled rate of ICI irAEs of any grade was 26.3% (95% CI 11.8-44.0), and the incidence of grade 3 or higher irAEs was 9.4% (95% CI 1.1-24.6). In multivariate analysis, the incidence, characteristics, and distribution of AEs varied by cancer type, combination therapy modality ( single/two-drug), and different agent types. Conclusion: Our meta-analysis summarizes AEs associated with ICI in digestive system cancers. The incidence, characteristics, and distribution of AEs vary by cancer type, combination therapy modality, and different agent types. These findings can be considered for the early identification of AEs and provide effective interventions to reduce the severity of these patients. It can provide a clinical reference and may contribute to clinical practice.